SENSOR DEVELOPMENT FOR HEMOGLOBIN CONCENTRATION MEASUREMENT BASED ON PHOLOPLETHYSMOGRAPHY - DEWANTORO (NIM: 13214065), PUTUT
Anemia is a condition when the number of red blood cells in the body is not enough to meet the needs of the body. In general, measurement of hemoglobin in the blood is done by taking blood samples invasively. In this final project, a device called Hemocare was created. Hemocare was a non-invasive device for measuring the hemoglobin concentration as a main component of red blood cell in the body. This device used photoplethysmography (PPG) method. The method was used to obtain the difference in the volume of blood that flows by using optical sensors. The acquired PPG raw signal required a signal conditioning circuit to obtain a good quality signal. In this final project, a signal conditioner in the form of filter and amplifier for the PPG signal was designed and tested. After initial conditioning the signal went through an ADC on microcontroller, which also made the calculation to get hemoglobin concentration. The calculation results were displayed through the display screen and sent to a smartphone via bluetooth. The implementation of the sensor used 4 lights with different wavelengths to obtain the PPG signal. This final project used wavelengths of 450nm, 515nm, 620nm and 940nm as a sensor. Based on the testing process, the filter circuit worked on a range from 0.6 to 4.8nm, while the gain of the amplifier worked on a range between 0 to 2000 times, which can be adjusted by potentiometer. The PPG signal can be acquired well by using a sampling frequency of 50Hz for each wavelength.